The limits of equal opportunity - Dubet, François (2013)
In recent decades, “equal opportunities” have been encroachingon another vision of socio-democratic system that the author calls “equal positions.” Those that advocate for equal opportunities – the U.S. model – are less concerned with reducing inequalities than they are with fighting against discrimination that prevents movement through the social structure based on personal merit. The paper argues that the left should combine equal positions with equal opportunities, but by prioritizing the former, which should not be confused with a conservative defense of the Welfare State as we know it today.